Real-Time Performance of Hybrid Mobile Robot Control Utilizing USB Protocol. (25th February 2015) - Augustyn, Jacek
This article discusses the problem of usability of the USB 2.0 protocol in the area of real-time control of a mobile robot. Optimization methods of data transfer handling were proposed. The impact of the optimization results on the entire system's performance was examined in practice. As a test-bed, a hybrid system composed of two devices communicating by direct USB connection was implemented. The first of the mentioned devices was a 32-bit SoC micro-system serving as a direct control unit, and the second one was an off-the-shelf PDA providing supervisory control and logging. Due to this design, the system meets regimes of the real-time constraints and maintains continuity of a data stream at a large bandwidth. The real-time performances of subsystems and the entire system were experimentally examined depending on various operating conditions. Thanks to the performed experiments, the dependency of real-time limits on operational parameters has been determined.